THE LEGAL STATUS OF CRIMEA AND SEVASTOPOL AND ADMINISTRATIVE REGULATION THEIR ACTIVITIES AT THE PRESENT STAGE - Fedor Vasiliev; Alexander Konyushok (Krymskij Naučnyj Vestnik, 2015)
In a state of law, all subjects of management in the conditions of development of market economy and socio-crisis extremism, economic and corruption) at the regional levels to ensure the implementation of Federal programs and objectives. On the other hand, the relevance of the issue under consideration is that the subjects of management of the Crimea and Sevastopol are both newly established (reorganized) independent territorial Executive authorities of the subjects of the Russian Federation with particular historical developments over the last two centuries (even in the whole historical epoch of the Russian Empire, the USSR, the RSFSR and Russia today).